Rethinking Jewishness in Weimar cinema (Berghahn Books, 2021)
"The burgeoning film industry in the Weimar Republic was, among other things, a major site of German-Jewish experience, one that provided a sphere for Jewish "outsiders" to shape mainstream culture. The chapters collected in this volume deploy new historical, theoretical, and methodological approaches to understanding the significant involvement of German Jews in Weimar cinema. Reflecting upon different conceptions of Jewishness - as religion, ethnicity, social role, cultural code, or text - these studies offer a wide-ranging exploration of an often overlooked aspect of German film history"-- Provided by publisher.
Keywords: Motion pictures -- Germany -- History -- 20th century.; Jews in the motion picture industry -- Germany.; Jewish motion picture producers and directors -- Germany.; Germany -- Civilization -- Jewish influences.; Cinéma -- Allemagne -- Histoire -- 20e siècle.; Juifs dans l'industrie cinématographique -- Allemagne.; Producteurs et réalisateurs de cinéma juifs -- Allemagne.; PERFORMING ARTS / Film & Video / History & Criticism; Civilization -- Jewish influences; Jewish motion picture producers and directors; Jews in the motion picture industry; Motion pictures; Germany; 1900-1999; History